Andragogy, Cognitive Learning, Experiential Learning and Booker T. Washington: The Unexplored Connection - Barnadette McKelly (Adult Education Research Conference, 2002)
The dominant discourse in the field of adult education has not explored a link between the adult learning philosophies of Booker T. Washington and dominant theories in the field of Adult Education. The purpose of this study is to investigate the link between the adult learning philosophies of Booker T. Washington and three of the dominant adult learning theories, androgogy, experiential learning and cognitive learning.